CONSTANCY CONDITION (INDICATORS) OF THE RATIO Z «PRICE / EARNINGS» OF COMPANIES - O. Zemlyanskiy (Вестник университета)
There offer the method of calculation and formula indicators, showing the condition of maintaining a constant ratio a year Z «price / earnings» of acquiring and has been acquired companies or any company on the market, with forecast growth of company profits.